Hereditary Protein C-Deficiency: Laboratory Values in Transmitters and Guidelines for the Diagnostic Procedure Report on a Study of the SSC Subcommittee on Protein C and Protein S - Pabinger, I; Allaart, C F; Hermans, J; Briët, E; Bertina, R M; The Protein C Transmitter Study Group (Thrombosis and Haemostasis, 1992)
A multicenter study on protein C-antigen and -activity values was carried out in transmitter patients with hereditary protein C deficiency (diagnosis established by pedigree analysis) and in normal controls in order to (1) establish the range of protein C levels in genetically determined heterozygotes and (2) to evaluate the usefulness of statistical procedures to discriminate between protein C deficient patients and controls. In transmitters absolute protein C activity values ranged from 19 to 82% and antigen values from 22 to 88.5%. Most transmitter patients could clearly be differentiated from the control group. However, in some transmitter patients values of protein C were within the range of the control group. The discrimination between transmitters and controls could be improved by statistical procedures. Using tolerance ellipses the overlapping area of the two groups was smallest when (factor II antigen + factor X antigen)/2 was plotted against protein C antigen. To specify the degree of uncertainty likelihood ratios were calculated to obtain the posterior probability for an individual for being deficient or not. In quadratic discriminant analysis the best discrimination between transmitters and controls was obtained using protein C activity versus factor X antigen and protein C antigen versus factor X antigen. Based on these analysis an equation was derived, which allows the calculation of the likelihood ratio favouring deficiency or non-deficiency in an individual.